Auschwitz : voices from the death camp - Deem, James M. (The Holocaust through primary sources, 2012)
"Examines Auschwitz, a death camp during the Holocaust, including its construction and daily workings, true accounts from prisoners of the camp and Nazi perpetrators, and how more than 1 million people were murdered there"--(Provided by publisher.)